Determinants of consumer buying behavior towards Nepali products - Regmi, Suman Kumar (Journal of Management and Development Studies, 2022)
This study has objected to locate the determinants affecting consumer buying behavior towards Nepalese industrial products in Nepal. Consumer Buying behavior is dependent variable and price fairness, accessibility, opinions, and status are the independents variables. The primary as well as secondary sources of data is used to reach the opinions of the respondents regarding price, availability, opinions, and position in Nepal. This study is based on respondents from particular area from Kathmandu Valley. To achieve the purpose of the study, structured questionnaires had been prepared. This study shows that price fairness is positively correlated to consumer buying behavior. It signifies the fair prices on Nepalese products leads to increase in consumer buying behavior. It indicates that higher the availability of Nepalese products, higher would be the consumer buying behavior. In addition to this, the study shows that status is positively related to consumer buying behavior. It indicates that an individual may have a very favorable decision toward purchasing Nepalese industrial products, if he/she believes that buying those products helps them to enhance their status to the society. The results also show that coefficients are positive for price fairness, availability, opinions, and prestige with consumer buying behavior. However, the coefficients are significant only for availability, opinions and prestige at 5 percent level of significance.